Adherence to the Mediterranean diet during pregnancy is associated with lower odds of excessive gestational weight gain and postpartum weight retention: results of the Mother-Infant Study Cohort. Issue 7 (14th October 2022) - Radwan, Hadia; Hashim, Mona; Hasan, Hayder; Abbas, Nada; Obaid, Reyad R. Shaker; Al Ghazal, Hessa; Naja, Farah
Abstract: During the first 1000 d of life, gestational weight gain (GWG) and postpartum weight retention (PPWR) are considered critical determinants of nutritional status. This study examined the effect of adherence to the Mediterranean diet (MD) during pregnancy on GWG and PPWR at 2 and 6 months among women in the United Arab Emirates (UAE), using data from the Mother-Infant Study Cohort. The latter is a prospective study, for which pregnant women were recruited ( n 243) during their third trimester and were followed up for 18 months. Data on socio-demographic characteristics and anthropometric measurements were obtained. An eighty-six-item FFQ was used to examine dietary intake during pregnancy. Adherence to the MD was assessed using the alternate MD (aMED) and the Lebanese MD (LMD). Adherence to the MD, PPWR2 (2 months) and PPWR6 (6 months) were considered high if participants belonged to the third tertile of the respective measures. Results indicated that 57·5 % of participants had excessive GWG while 50·7 % and 45 % retained ≥ 5 kg at 2 and 6 months postpartum, respectively. After adjustment, adherence to both MD scores was associated with lower odds of excessive GWG (aMED, OR:0·41, 95 % CI:0·18, 0·93; LMD, OR:0·40, 95 % CI: 0·16, 0·98). Adherence to MD was also associated with PPWR2 (aMED: OR: 0·23, 95 % CI: 0·06, 0·88) and PPWR6 (aMED OR:0·26; 95 % CI:0·08–0·86; LMD, OR:0·32; 95 % CI: 0·1, 0·98). The findings of this study showed that adherence to the MD may reduce GWG and PPWR and, hence, underscored the importance of promoting the MD for better health of the mother and infant.